BORON ISOTOPE GEOCHEMISTRY DURING DIAGENESIS. PART I. EXPERIMENTAL DETERMINATION OF FRACTIONATION DURING ILLITIZATION OF SMECTITE - Williams L.B.; Hervig R.L.; Holloway J.R.; Hutcheon I. (My University, 2001)
Experiments were performed to measure the isotopic fractionation of boron between illite/smectite (I/S) clay minerals and water as a function of temperature (300° and 350°C) and degree of illitization. Corresponding changes in the oxygen isotopes were monitored as an indication of the approach to equilibrium. The kinetics of the B-isotope exchange follows the mineralogical restructuring of smectite as it recrystallizes to illite. An initial decline in δ11BI/S occurs when the I/S is randomly ordered (RO). The δ11BI/S values reach a plateau during R1 ordering of the I/S, representing a metastable condition. The greatest change in δ11BI/S is observed during long-range (R3) ordering of the I/S when neoformation occurs.Values of δ11BI/S measured on the equilibrium reaction products were used to construct a B-isotope fractionation curve. There is a linear correlation among data from these experiments and 1100°C basaltic melt-fluid fractionation experiments (Hervig and Moore, 2000) that can be extrapolated to include adsorption experiments at 25°C (Palmer et al., 1987). Unlike other stable isotopic systems (e.g., oxygen) there is no mineral-specific fractionation of B-isotopes, but rather a coordination dependence of the fractionation. Under diagenetic conditions B is predominantly in trigonal coordination in fluids but substitutes in tetrahedral sites of silicates. The preference of 10B for tetrahedral bonds is the major fractionating factor of B in silicates.